The Information Context of Moral Rights Under the Copyright Regime - Wilkinson, Margaret Ann; Gerolami, Natasha (Proceedings of the Annual Conference of CAIS / Actes du congrès annuel de l'ACSI, 2013)
Moral rights have not been so uniformly or widely adopted as economic copyrights for authors, perhaps because the actual and potential value of moral rights in ensuring information needs are met has gone unrecognized. The authors demonstrate that moral rights protection can enhance authority control in the new information environment. Le droit moral n'a jamais été adopté aussi uniformément ou largement que le droit d'auteur, vraisemblablement parce la valeur réelle et potentielle du droit moral dans le respect des besoins informationnels est passée inaperçue. Les auteurs démontrent que la protection du droit moral peut améliorer le contrôle dans le nouvel environnement de l'information.